Functional Brain Mapping and the Endeavor to Understand the Working Brain - Signorelli, Francesco; Chirchiglia, Domenico (IntechOpen, 2013)
Functional brain mapping has by now gained a high impact on research and clinical practice: huge funds are unveiled all over the world in order to boost the research and clinical applications of this field of neuroscience. The most successful approach to unlock the mysteries of the brain, to tell it with Jay Ingram, is to bring together an interdisciplinary network of scientists and clinicians and encourage an interchange of ideas. It is this crossfire we try to promote with this book.